Influence of aging pathways on the evolution of heterogeneous solute-rich features in peak-aged Al-Mg-Si-Cu alloy with a high Mg/Si ratio. (1st February 2019) - Guo, M. X.; Zhang, Y. D.; Yuan, B.; Sha, G.; Zhang, J. S.; Zhuang, L. Z.; Lavernia, E. J.
ABSTRACT: We report on a study of the influence of aging pathways on the evolution of solute-rich features in peak-aged Al-Mg-Si-Cu alloys. The concentration and partitioning ratios of Mg, Si and Cu and Mg/Si ratios in the heterogeneous solute-rich features all increase with increasing size, with Si exhibiting the highest partitioning ratio, but notably these ratios change dramatically depending on the aging pathway selected. Accordingly, the short-time age hardening response can be enhanced by promoting both homogeneous and heterogeneous precipitate nucleation, while simultaneous improvements in peak-aged strength and elongation can be attained by a vacancy-assisted aging pathway.